The Strategies to Strengthen Interprofessional Competence Through Emergency Simulations in Primary Healthcare Facilities: Strategies to Strengthen Interprofessional Competence Through Emergency Simulations in Primary Healthcare Facilities - Anna, Romauli (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Primary healthcare facilities play a crucial role in handling emergency cases that require quick response and effective coordination among healthcare professionals. Strengthening interprofessional competencies through medical simulation has become a key strategy in improving communication skills, team coordination, and decision-making effectiveness in emergency situations. This study employs a quasi-experimental method involving various healthcare professions in realistic scenario-based emergency simulations. The results indicate that after attending the simulation training, there was a significant improvement in team communication, coordination, and decision-making effectiveness. Simulations not only enhance healthcare workers’ preparedness in handling emergency cases but also contribute to reducing medical errors. Therefore, this method is recommended for widespread implementation in primary healthcare facilities to improve emergency service quality.